2018
DOI: 10.1128/jvi.00433-18
|View full text |Cite
|
Sign up to set email alerts
|

Avian Influenza Viruses in Wild Birds: Virus Evolution in a Multihost Ecosystem

Abstract: Wild ducks and gulls are the major reservoirs for avian influenza A viruses (AIVs). The mechanisms that drive AIV evolution are complex at sites where various duck and gull species from multiple flyways breed, winter, or stage. The Republic of Georgia is located at the intersection of three migratory flyways: the Central Asian flyway, the East Africa/West Asia flyway, and the Black Sea/Mediterranean flyway. For six complete study years (2010 to 2016), we collected AIV samples from various duck and gull species… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 49 publications
2
86
1
Order By: Relevance
“…Of the many potential environmental factors that may be associated with the onset of PM/DM, infection could be a plausible explanation for this time-space clustering at disease onset. 4 5 In this regard, it has been recognised that some infectious agents can be transmitted by vectors inhabiting near freshwater, whose activity depends on the season, such as mosquitos and migratory birds, 15 16 although it is just a hypothesis of potential environmental factors related to anti-MDA5-associated ILD. On the other hand, recognition of viral RNA by MDA5 initiates activation of NF-κβ and production of type I interferon (IFN) and other proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Of the many potential environmental factors that may be associated with the onset of PM/DM, infection could be a plausible explanation for this time-space clustering at disease onset. 4 5 In this regard, it has been recognised that some infectious agents can be transmitted by vectors inhabiting near freshwater, whose activity depends on the season, such as mosquitos and migratory birds, 15 16 although it is just a hypothesis of potential environmental factors related to anti-MDA5-associated ILD. On the other hand, recognition of viral RNA by MDA5 initiates activation of NF-κβ and production of type I interferon (IFN) and other proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…The samples were tested at the Erasmus Medical Center for the presence of avian influenza A viruses using matrix gene specific, and H5 and H7 HA gene specific real-time RT-PCR (RRT-PCR) assays with a cut-off for negative samples set at a cycle threshold (Ct) value of 40 on the basis of the findings for multiple amplification curves as previously described [13]. Only positive samples were inoculated in two 11-day-old embryonated chicken eggs for 3 days (no blind passaging) and sequenced using Sanger (Thermo Fisher Scientific, Waltham, MA, USA) and MinION (Oxford Nanopore Technologies, Oxford, United Kingdom) techniques as previously described [14,15]. Samples were collected using sterile swabs, transferred into 2 mL viral transport medium as described previously [12], and samples were stored at −80 °C until shipped and processed.…”
Section: Virus Detection Isolation Characterisation and Sequencingmentioning
confidence: 99%
“…The proposed IAV MinION sequencing protocol could easily be introduced into existing laboratory environments and allow direct, rapid and costefficient identification of diverse IAV strains. In addition, this protocol allows high-throughput sequencing of, for example, AIV samples from passive surveillance studies, shown to be of great importance for the molecular epidemiology of the worldwide AIV situation [14,15].…”
Section: Discussionmentioning
confidence: 99%